Theoretical and Applied Aspects of Modern Management of Educational Institutions - Marmaza, Oleksandra (Pedagogical Discourse, 2025)
The article notes that the study of management models aimed at the efficient functioning and sustainable development of educational institutions in the postwar period is of particular relevance. It is proved that this will contribute to the formation of a quality educational environment and the development of human capital in the country as a whole. In accordance with this goal, theoretical and applied aspects of the state of management of an educational institution at the present stage are revealed; the relevance of the problem of studying traditional and innovative approaches to management due to the challenges of time and turbulence of the environment is substantiated; the peculiarities of the requirements for management and the head of an educational institution from the point of view of the present and development prospects are clarified. The main challenges of managing an educational institution at the present stage in Ukraine are identified: the consequences of hostilities (destruction of infrastructure, the need to organize training in conditions of danger, psychological trauma of participants in the educational process, significant educational losses); instability of financing and economic difficulties; personnel problems (outflow of teachers, the need to improve their skills in the context of reforms and technologization); ensuring quality distance and blended learning; overcoming educational losses caused by war and previous crises. Through the integrated use of theoretical methods, which included the analysis of the source base and practical experience on the problem, systematization and synthesis of approaches to its solution, generalization and formulation of conclusions, we have identified the following among the key aspects of the current state of management of an educational institution: humanistic, systemic, innovative, participatory, digital approaches.